KOTA HUTAN IBU KOTA NUSANTARA DALAM MODEL DESAIN RAMAH LINGKUNGAN - Wangke, Freddy; Paulus, Jeanne Martje (Pusat Studi Pembangunan Pertanian dan Pedesaan (PSP3) dan Ilmu Pengelolaan Sumberdaya Alam dan Lingkungan (PSL), 2024)
The Archipelago Capital (IKN) as the new capital is on the island of Kalimantan, replacing Jakarta. The IKN development carries the forest city concept which pays attention to environmentally friendly aspects. This writing aims to apply the International Environmental Organization Program in the model and form transmission mechanism and apply the Law of the Republic of Indonesia Number 32 of 2009 in the model and form the transmission mechanism. The endogenous and exogenous variables required for simultaneous equations are by theory and empirical experience. The model built consists of 16 endogenous variables (G) and 29 predetermined variables. This means that in model (K) there are 45 variables. There are 14 exogenous and 16 endogenous variables, so (M) totals 30 variables. Thus, (K – M) = (G – 1). This means that the model is identified precisely and is suitable for analysis using the Two Stage Least Squares Method. Application of the International Environmental Organization Program, namely establishing the International Eco Green University to function in the field of research, development and preservation of flora, fauna and marine biota endemic to the island of Kalimantan. The application of the Environmental Law is realised starting from the process of providing residential or office infrastructure in the form of condominiums to the technology for processing liquid and solid waste materials into organic materials for agricultural fertiliser, biogas, animal feed and land fisheries. The transmission mechanism is from achieving added value in all business fields to the growth of IKN's Gross Regional Domestic Product.